RANCANG BANGUN ALAT PENGGULUNG KAWAT EMAIL UNTUK KUMPARAN MOTOR MENGGUNAKAN MIKROKONTROLLER ATMEGA328 SEBAGAI UNIT PENGENDALI - Valdi Rizki Yandri; Desmiwarman Desmiwarman (Situs resmi ITP Press, 2016)
Application of automation in the production process at this point is very helpful, easy and can be used to cover the human limitations in increasing the productivity better. Application of automation is very suitable for secondary industry, because, automation is inexpensive and can be realized only with a computer device can even be stored on a chip that stores various kinds of commands as a controller equipment you want to control, of course, with the right program. One application can be applied to the coil wire roller by utilizing the microcontroller ATmega328 as the unit will store the control command to specify the amount of the roll, set the pace rolling, and stop rolling. With the keypad as the input number of reels, set the speed of the rolling process by using pot to change the value of the PWM, and a limit switch as a unit calculating the number of rolls, after the suppression amount is equal to the value of the limit switch input, the process will stop. Once embodied in a tangible form, this tool can work well, the input values 25 rolls dihasilkann much as 25 rolls with PWM 150, but a mechanical fault suppression limit switch occurs at high speed, the difference between the input value and the results can be within 4 pieces of excess rolls the PWM value of 255